Práticas ambientais nas etapas de geração de matériaprima e de produção em empresas paulistas processadoras de madeira - Bernardo, Júlio Samuel Sávio (Universidade Federal de São Carlos, 2009)
Wood processing companies can, potentially, generate environmental impacts such as wood, water, and energy consumption, and soil, air, water, and noise pollution. In order to conserve the environment, it is necessary that companies adopt environmental practices, i.e., practices for reducing or avoiding environmental impacts. The objective of this study was to analyze the environmental practices adopted by São Paulo state wood processing companies in the stages of generating and acquiring raw material and product production. The complementary objectives were: 1) investigate how the environmental practices adopted influence aspects of production and products attributes; 2) identify the tools used to support the environmental management; 3) identify the major motivating factors that led the adoption of the environmental practices. A qualitative study was carried out in 5 São Paulo state companies that produce wooden products for writing, cellulose and paper, or recycled corrugated fiberboard packaging. The research methodology adopted was case studies. Several interviews were conducted and documents were analyzed, among which are the Sustainability Reports, the Plan of Forest Handling, and other information disclosed on the companies websites. It can be said that the environmental practices adopted by the majority of the companies studied refer to the consumption of wood, water, and energy, and to the pollution of the soil, air, and water. These practices are examples of real solutions found by the companies, and can be the frame of reference for other wood processing companies. In order to improve the environmental performance, it is recommended that each company should evaluate the need and possibility of employing practices mentioned in the literature but that have not been adopted by any of them. Another recommendation is that the companies should improve some environmental practices they have already adopted. In most of the companies, the production cost was increased mainly due to the investments in machinery and equipment. In some companies the price of the final product was raised. Nevertheless, the acceptability of the products in the corporative national and/or international market was increased. The majority of the companies use internally developed tools to support the environmental management. It is recommended that the companies make an effort to attract external support for the continuous improving of the existing tools and also for the development of new tools. It could be concluded that the major motivating factors for the adoption of environmental practices are legislation, market regulation, and factors related to business competitiveness such as the improvement of the environmental image and the possibility of costs reduction.
Keywords: Engenharia de produção; Gestão ambiental; Impacto ambiental; Ciclo de vida do produto; Processamento de madeira; Práticas ambientais; ENGENHARIAS::ENGENHARIA DE PRODUCAO